War-related trauma and posttraumatic stress disorder in refugees, displaced, and nondisplaced people during armed conflict in Sudan: a cross-sectional study - Khadija A. Khalil; Galia Tajelsir Fadulelmula Mohammed; Ahmed Balla M. Ahmed; Salma S. Alrawa; Hager Elawad; Amna A. Almahal; Radia F. Mohamed; Eithar M. Ali (Conflict and Health, 2024)
Abstract Background The ongoing armed conflict in Sudan has caused mass displacement, affecting mental health. This study aimed to assess the prevalence of posttraumatic stress disorder (PTSD) and trauma among refugees, internally displaced, and nondisplaced people, while also examining the link between displacement type, PTSD severity, and associated factors. Methods This cross-sectional study used the Posttraumatic Stress Disorder Checklist for DSM-5 to assess PTSD symptoms and the General Health Questionnaire-28 to evaluate depression. Data were collected from 642 participants, targeting general social media groups for those within Sudan and specific groups for refugees outside the country. Sociodemographic and trauma event data were also gathered. Data analysis was conducted using SPSS, applying one-way ANOVA and independent t-tests to compare PTSD and depression. Binary logistic regression identified associations between sociodemographic factors and PTSD symptoms. Results Among the 642 participants, 46.3% were internally displaced people (IDP), 42.1% were refugees, and 11.7% were non-displaced individuals. Clinically significant PTSD symptoms were identified in 36.6% of the participants. Refugees had a significantly greater percentage of traumatic events (M = 4.31, SD = 2.605, p < .01). Depression symptoms were found to be strongly associated with clinically significant PTSD (p < .001). Factors significantly linked to depression symptoms included female gender (p = 0.015), being single (p = 0.048), younger age (p = 0.036), dissatisfaction with living conditions (p < 0.001), and unemployment (p = 0.021). Dissatisfaction with living conditions also significantly influenced the likelihood of developing PTSD (p < .001). Conclusion The study found that 36.6% of participants experienced PTSD, with refugees having a 1.4 times greater risk of developing PTSD compared to IDP and non-displaced individuals. Traumatic events were moderately correlated with PTSD symptoms, though non-displaced individuals had higher exposure to such events. These findings highlight the need for targeted mental health interventions, particularly for refugees and those affected by traumatic events. Further research using probability sampling is necessary to confirm these results and inform more effective mental health policies and programs for displaced populations.